Women in economics in CEE - Andrea Kiss; Barbara Pertold-Gebicka; Ágnes Szabó-Morvai (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
This paper shows descriptive evidence about the gender disparities in economics profession in three Visegrad countries. We show that the employment gender gap in highly ranked institutions is in par with the gap found in the United States and in other Western countries. However, the gap is smaller and sometimes even reversed at lower ranked institutions. To the extent that these patterns are due to institutional constraints - as suggested by previous literature - making academia more inclusive would have a potential to close the gap in higher ranked institutions. Some practical suggestions are discussed.
Keywords: 330; economics; female